Emotional Intelligence and Resistance to Change: Mediating role of Psychological Capital in Telecom Sector of Pakistan (Pakistan Journal of Commerce and Social Sciences (ISSN 1997-8553), 2015)
Emerging research on positive psychological resources has identified Psychological Capital (PsyCap) as an important contributor towards a number of useful organizational outcomes. Literature on change management suggests that one of the most significant obstacles in managing change is employees’ inability to accept the change initiatives, and that emotional intelligence (EI) and PsyCap both support in combating resistance towards change (RTC). Based on the importance of the three interrelated concepts, the present study is aimed to examine the mediating role of psychological capital on the relationship between emotional intelligence and resistance towards change. Data has been collected from a sample of 170 employees from telecom organizations operating in Pakistan through personally administered questionnaires. The mediation effect has been tested using Baron and Kenny’s method of hierarchical multiple regression. Results show a positive relationship between EI and PsyCap, a negative relationship between PsyCap and resistance towards change and a negative relationship between emotional intelligence and the resistance toward change. Finally, PsyCap fully mediated the relationship between emotional intelligence and resistance towards change. The study makes a significant and unique contribution to literature by showing the mediation effect of PsyCap between the relationship of EI and RTC, which has been explored for the first time. Also, the study establishes that significant relationships exist between EI, PsyCap and RTC individually in the unique context of telecom sector of Pakistan. It is concluded that emotional intelligence leads to stronger psychological resources which play a significant role in employee’s proactive attitudes towards change. Finally, limitations, future research and practical implications have been discussed.